OPTIMASI TEMPERATUR YANG MEMPENGARUHI KEKERASAN PADA PEMBUATAN BALL MILL DENGAN CARA HOT ROLLING - Santhi Wilastari (P3M Politeknik Negeri Cilacap, 2018)
Violence is one of the characteristics needed by the ball mill. To get this trait up to now is still done by trial and error so it is very ineffective. Therefore, a study was conducted to determine the parameters that affect the hardness of the ball mill and the optimal level. There are three parameters that are thought to affect ball mill hardness, namely the temperature of raw material (Tm), the initial temperature of the quenching process (Tq) and the final temperature of the quenching process (Tt).